Overpressure/ Depositional Analysis of Parts of Onshore (X-Field) Niger Delta Basin Nigeria, Based on Well Logs Data (2016)
Overpressure in the world’s sedimentary basins are known to be allied with permeability barriers, tectonics, shale digenesis, basin structure and undercompaction factors. The Niger Delta basin has many overpressured zones with different depositional enviroments. This study was done using six drilled wells log suits in an x- field (Gama ray log, deep induction log, Density log, and sonic log). The data was acquired from Cheveron Nigeria Ltd in ascii softcopy format, which was analysed using both manual method and computer processed interactive petrophysics (IP) version 3.6 software. The logs were loaded and printed to hardcopies and digitization done at 5m interval to extract the data across the log suits. Characteristic curve patterns along the gamma log were delineated for shape patterns such as bell shape, funnel shape, and blocky to reveal paleoenviroments of the study area. The results indicate twenty one (21) overpressure zones within the wells, three (3) subsurface overpressure zones are correlated across the wells at depth interval between 3000m – 3200m for wells A,B,C,D,E and 2900m – 3000m for wells E and C , and 3600m – 3700m for wells C and F respectively,these overpressured zones occurred within a dominantly fluvial channel with minor detlaic distribution and barrier bar complexes. The areas identified as overpressured zones should be critically examined during drilling to avoid rig blow outs.